Inhibition of biological TCE and sulphate reduction in the presence of iron nanoparticles. - Barnes, R; Riba, O; Gardner, M; Singer, A; Jackman, SA; Thompson, I (2010)
Iron (Fe) nanoparticles are increasingly being employed for the remediation of Chlorinated Aliphatic Hydrocarbon (CAH) contaminated sites. However, these particles have recently been reported to be cytotoxic to bacterial cells, and may therefore have a negative impact on exposed microbial communities. The overall objective of this study was to investigate the impact of Fe nanoparticles on the biodegradation of CAHs by an indigenous dechlorinating bacterial community. Also, to determine the most appropriate combination and/or application of bimetallic (Ni/Fe) nanoparticles and dechlorinating bacteria for the remediation of CAH contaminated sites. Addition of Fe nanoparticles to groundwater collected from a CAH contaminated site in Derby, UK, led to a decrease in the oxidation-reduction potential (ORP) and an increase in pH. The biological degradation rate of TCE was observed to progressively decrease in the presence of increasing Fe nanoparticle concentrations; which ranged from 0.01 to 0.1 gL(-1), and cease completely at concentrations of 0.3 gL(-1) or above. Concentrations greater than 0.3 gL(-1) led to a decline in viable bacterial counts and the inhibition of biological sulphate reduction. The most appropriate means of combining bimetallic (Ni/Fe) nanoparticles and indigenous dechlorinating bacteria was to employ a two step process: initially stimulating the biodegradation of TCE using acetate, followed by the addition of bimetallic nanoparticles to degrade the remaining cis-1,2-DCE and VC.